Tackling Housing Challenges in Vulnerable Communities: Sustainable Construction Using Recycled PET Plastic Bricks - Ayala, Sebastián; Diaz, Valentín; Grippo, Genaro (Inglés II. Universidad Tecnológica Nacional. Facultad Regional Paraná, 2024)
Abstract— Inadequate housing affects over 1.8 billion people globally and poses significant risks to human dignity and public health. Despite being a fundamental human right, many individuals face eviction and homelessness. To combat this crisis, sustainable construction technologies, particularly those utilizing recycled plastics, offer a dual solution: mitigating the housing shortage while managing environmental waste. This study aims to evaluate the impact of using recycled materials in housing construction, focusing on its effectiveness in areas with severe housing deficits. This paper is organized into three main sections: contextualizing the housing crisis, analyzing its causes and consequences, and presenting and assessing the proposed solution. By examining reliable data and evaluating the feasibility of this innovative approach, the study seeks to provide engineers and stakeholders with actionable insights into sustainable and efficient housing solutions. Ultimately, this research is expected to contribute to both addressing urgent social needs and advancing sustainable development goals.

Resumen— La falta de acceso a una vivienda digna afecta a más de 1.800 millones de personas en todo el mundo y plantea riesgos importantes para la dignidad humana y la salud pública. A pesar de ser un derecho humano fundamental, muchas personas se enfrentan al desalojo y a la falta de vivienda. Para combatir esta crisis, las tecnologías de construcción sostenible, en particular aquellas que utilizan plásticos reciclados, ofrecen una solución dual: mitigar la escasez de viviendas y al mismo tiempo gestionar los residuos ambientales. Este estudio tiene como objetivo evaluar el impacto del uso de materiales reciclados en la construcción de viviendas, centrándose en su efectividad en zonas con déficit habitacional severo. El trabajo se organiza en tres secciones principales: contextualizar la crisis inmobiliaria, analizar sus causas y consecuencias, y presentar y valorar la solución propuesta. Al examinar datos confiables y evaluar la viabilidad de este enfoque innovador, el estudio busca brindar a los ingenieros y partes interesadas conocimientos prácticos sobre soluciones de vivienda sostenibles y eficientes. En última instancia, se espera que esta investigación contribuya tanto a abordar necesidades sociales urgentes como a promover objetivos de desarrollo sostenible.
Keywords: Inglés II; decent housing; plastic waste; recycled PET plastic bricks; vivienda digna; desechos plásticos; ladrillos de plástico PET reciclado